Functional magnetic resonance imaging in primary hyperparathyroidism. Issue 1 (July 2020) - Gazes, Yunglin; Liu, Minghao; Sum, Melissa; Cong, Elaine; Kuo, Jennifer; Lee, James A; Silverberg, Shonni; Stern, Yaakov; Walker, Marcella
Abstract : Objective: The neurophysiological mechanisms underlying cognitive dysfunction in primary hyperparathyroidism (PHPT) and the brain regions affected are not clear. We assessed neural activation during cognitive testing (matrix reasoning, paired associates, and logical memory) using functional MRI (fMRI) in 23 patients with PHPT and 23 healthy controls. A subset with PHPT was re-assessed 6 months post-parathyroidectomy (PTX). Design: This is an observational study comparing neural activation by fMRI in patients with PHPT to normative controls. Postmenopausal women were studied at a tertiary referral center. Results: There were no between-group differences in cognitive task performance. Patients with PHPT had lower neural activation vs controls (max Z = 4.02, all P < 0.01) during matrix reasoning in brain regions involved in executive function (left frontal lobe (k = 57) and right medial frontal gyrus (k = 72)) and motor function (right precentral gyrus (k = 51)). During paired associates (verbal memory), those with PHPT had greater activation in the right inferior parietal lobule (language/mathematical operations; k = 65, P < 0.01). Greater activation in this region bilaterally correlated with higher PTH (k = 96, P < 0.01). Post-PTX, activation decreased during matrix reasoning, but in different regions than those affected pre-PTX. Conclusions: PHPT is associated with differences in task-related neural activation patterns, but no difference in cognitive performance. While this may indicate compensation to maintain the same cognitive function, there was no clear improvement in neural activation after PTX. Larger, longitudinal studies that include PHPT patients followed without surgery are needed to determine if PTX could prevent worsening of altered neural activation patterns in PHPT.